2005
DOI: 10.1007/s00467-005-2141-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis: possible association with cytomegalovirus infection

Abstract: Sirs, A previously healthy 14-year-old boy presented with mild acute renal dysfunction with proteinuria and glucosuria. His past history and family history were unremarkable. The ophthalmologic examinations were normal. The patient was taking no medicines. Blood urea nitrogen of 18 mg/dl, creatinine of 1.3 mg/dl and creatinine clearance of 107.4 ml/min/1.73 m 2 were all measured. An autoantibody screen was negative. Urinary excretion of N-acetyl-beta-glucosaminidase (NAG) was 63.2 U/l (normal 0.3-11.5 U/l), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…All of the reported cases were treated with ganciclovir, which was discontinued in one patient due to its side effects [19][20][21]. There are also two reports of pediatric patients, a 3-month old baby and a 14-year-old boy, with interstitial nephritis associated with CMV infection [22,23]. Το the best of our knowledge, we report here the first published case of biopsy-proven, CMV-related membranous glomerulonephritis in an immunocompetent child.…”
Section: Discussionmentioning
confidence: 67%
“…All of the reported cases were treated with ganciclovir, which was discontinued in one patient due to its side effects [19][20][21]. There are also two reports of pediatric patients, a 3-month old baby and a 14-year-old boy, with interstitial nephritis associated with CMV infection [22,23]. Το the best of our knowledge, we report here the first published case of biopsy-proven, CMV-related membranous glomerulonephritis in an immunocompetent child.…”
Section: Discussionmentioning
confidence: 67%
“…CMV has been implicated in nephritis and rejection in renal transplant recipients [De Keyzer et al, 2011]. Additionally, it has been suggested that CMV may be involved in childhood nephritis [Platt et al, 1985;Matsukura et al, 2006;Georgaki-Angelaki et al, 2009] and congenital nephrotic syndrome [Evans and Lyon, 1991;Batisky et al, 1993;Giani et al, 1996;Eddleston et al, 1997;Barbi et al, 1998;Frishberg et al, 2003;Besbas et al, 2006]. Since children with renal disease are treated generally by immunosuppressive drugs, these patients are considered to be at high risk for reactivation of herpesviruses.…”
Section: Introductionmentioning
confidence: 99%
“…TIN is a heterogeneous disorder caused by infection, immunological disorders or drugs. Infection by a wide range of organisms is the most common cause of TIN [ 8 ]. Human immunodeficiency virus, cytomegalovirus, Epstein–Barr virus, Hanta virus, Polyoma and adenovirus are some of the viruses associated with TIN.…”
Section: Discussionmentioning
confidence: 99%